Radiographic Outcomes of Plate vs Screw Constructs in Open Reduction and Internal Fixation of Calcaneus Fractures via the Sinus Tarsi Approach. Issue 4 (16th October 2019) - Pitts, Charles; Almaguer, Adam; Wilson, Jack; Johnson, Michael
Category: Hindfoot, Trauma Introduction/Purpose: Intra-articular fractures of the calcaneus are a common injury to the hindfoot following high energy trauma to the lower extremity. Treatment of these fractures has evolved. Due to the concern of wound complications associated with extensile open treatments, smaller incision techniques, such as the sinus tarsi approach, are increasing in popularity. A number of fixation strategies are utilized with this approach, and it is unknown which most accurately restores radiographic alignment. The purpose of this study is to compare the postoperative radiographic outcomes of a plate and screw construct versus a cannulated screw construct when using the sinus tarsi approach for open reduction and internal fixation (ORIF) of calcaneus fractures. Methods: After IRB approval, records for all patients treated surgically at our institution for calcaneus fractures from 2012 to 2017 were reviewed. Inclusion criteria were intra-articular calcaneus fractures, patients aged 18 years or older, and use of the sinus tarsi approach. Exclusion criteria were open fractures and clinical follow up less than 6 weeks. A total of 51 fractures underwent ORIF using cannulated screws alone (Group 1), and 23 fractures underwent ORIF using a sinus tarsi plate (Group 2). The primary outcomes of interest included pre- and postoperative Bohler and Gissane angles, wound complications, and unplanned return to OR. Results: There was no statistically significant difference between preoperative Bohler angles for Group 1 (14.5 degrees) versus Group 2 (12.3 degrees) (p=0.35), nor was there a significant difference between postoperative Bohler angles between Group 1 (30.1 degrees) and Group 2 (27.0 degrees) (p=0.09). Similarly, preoperative Gissane angles for Group 1 (128.4 degrees) and Group 2 (134.5 degrees) (p=0.17) and postoperative Gissane angles for Group 1 (116.7 degrees) and Group 2 (118.8 degrees) (p=0.44) showed no statistically significant difference. There were a total of 3 wound complications in Group 1 versus 2 wound complications in Group 2 (p=0.76). There was no statistically significant difference in operative duration (p=0.97) or the number of unplanned returns to the OR between the two groups (p=0.77). Conclusion: When comparing the cannulated screw and plate and screw fixation techniques, there was no difference in restoration of the Bohler and Gissane angles. Both techniques had similar rates of postoperative complications and return to the OR. Our data suggests that fixation using cannulated screws alone versus sinus tarsi plate provide similar radiographic outcomes and risk of complications. The two techniques are also similar in terms of implant costs. Our results indicate that either technique effectively improves radiographic parameters.